2001
DOI: 10.1179/026708301101510483
|View full text |Cite
|
Sign up to set email alerts
|

Review of creep behaviour of AZ91 magnesium alloy produced by different technologies

Abstract: The available studies of the creep behaviour of AZ91 alloy produced by die casting, ingot casting, or thixoforming are reviewed in the present paper. Differences in microstructure and creep response are analysed and discussed with a view to providing a unitary, comprehensive description of the creep behaviour of this material. In particular, the minimum creep rate dependence on applied stress is described by means of a modified form of power law, which takes into consideration the effects of grain size and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 11 publications
5
25
1
Order By: Relevance
“…They suggested that the low-stress creep behavior was related to grain boundary migration and sliding, which was accompanied by discontinuous precipitation of ␤-Mg 17 Al 12 from the supersaturated ␣-Mg matrix. A recent review paper [13] compared the creep behavior of AZ91 alloys produced by different technologies. The difference in creep response was rationalized qualitatively by microstructural factors such as grain size and intragranular precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the low-stress creep behavior was related to grain boundary migration and sliding, which was accompanied by discontinuous precipitation of ␤-Mg 17 Al 12 from the supersaturated ␣-Mg matrix. A recent review paper [13] compared the creep behavior of AZ91 alloys produced by different technologies. The difference in creep response was rationalized qualitatively by microstructural factors such as grain size and intragranular precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…3,54) Although reliable estimation of the creep resistance for many kinds of die-cast and conventionally cast Mg alloys exists, no information is available for other wrought Mg alloys intended to be used as sheets, rods, or pipes. As typical for Mg alloys, the creep behavior at elevated temperature can be described by following power law relationship:…”
Section: )mentioning
confidence: 99%
“…Because of the characteristics in the process of magnesium injection, this method forces the melt material to take continuously a shear force while acting on a temperature. A property of the material in a semi-solid state under shear stress appears to be low viscosity as a perfectly melting state [4,5,6]. In addition, a thixo-tropic state, at which the viscosity varies reversibly according to the presence or absence of stress, is exposed.…”
Section: Introductionmentioning
confidence: 99%